Design and validation of a medical robotic device system to control two collaborative robots for ultrasound-guided needle insertions - Berger, Johann; Unger, Michael; Keller, Johannes; Reich, C. Martin; Neumuth, Thomas; Melzer, Andreas (Frontiers in Robotics and AI, 2022)
The percutaneous biopsy is a critical intervention for diagnosis and staging in cancer therapy. Robotic systems can improve the efficiency and outcome of such procedures while alleviating stress for physicians and patients. However, the high complexity of operation and the limited possibilities for robotic integration in the operating room (OR) decrease user acceptance and the number of deployed robots. Collaborative systems and standardized device communication may provide approaches to overcome named problems. We designed and validated a medical robotic device system to access and control a collaborative setup of two KUKA robots for ultrasound-guided needle insertions. The system is based on a novel standard for service-oriented device connectivity and utilizes collaborative principles to enhance user experience. Implementing separated workflow applications allows for a flexible system setup and configuration. The system was validated in three separate test scenarios to measure accuracies for co-registration and needle target planning in a water bath and in an abdominal phantom. The positioning errors in the phantom ranged from 1.69 ± 0.92 mm to 1.96 ± 0.86 mm, depending on the setup. The presented results serve as a proof-of-concept and add to the current state of the art to alleviate system deployment and fast configuration for percutaneous robotic interventions.